Graphene oxide sol for anodic oxidation treatment of aluminum alloy and application of graphene oxide sol

By combining two-component silane modified silica sol and titanium sol, the dispersion and adhesion of graphene are optimized, and the corrosion resistance caused by the pores of oxide films in the anodized treatment of aluminum alloy is solved, achieving efficient and environmentally friendly corrosion resistance.

CN119776946APending Publication Date: 2025-04-08ZHONGLIHONG (SHENZHEN) NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510211890.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the prior art In the anodizing treatment of aluminum alloy, the oxide film has tiny pores, resulting in insufficient corrosion resistance, and traditional pore sealing technology has problems such as poor sealing effect, complex process, and environmental pollution.

Method used

By combining two-component silane-modified silica sol with titanium sol, the dispersion and adhesion of graphene are optimized, and the preparation process is simplified to form an improved graphene pore sealing technology.

Benefits of technology

It improves the dispersion and adhesion of graphene oxide, enhances the corrosion resistance of the aluminum alloy surface, reduces process complexity and environmental pollution, and provides an environmentally friendly, efficient and economical solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses graphene oxide sol for aluminum alloy anodic oxidation treatment and application of the graphene oxide sol. According to the invention, through the combination of the bi-component silane modified silica sol and the titanium sol, the dispersibility of graphene is optimized, the adhesive force of the graphene is enhanced, and the preparation process is simplified, so that the limitation of the prior art is overcome, and an environment-friendly, efficient and economical aluminum alloy corrosion-resistant solution is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal material surface treatment, and in particular to a sol used for anodizing of aluminum alloy and application thereof. Background Art

[0002] In a humid and corrosive environment, Al alloys are prone to corrosion, which affects their service life and performance. In order to improve the corrosion resistance of aluminum alloys, anodizing is usually used to form a dense oxide film on the surface of the aluminum alloy. However, there are often many tiny pores on this oxide film, which can easily become channels for corrosion by corrosive media, reducing the protective effect of the oxide film. In order to seal these pores and improve the corrosion resistance of the oxide film, people have developed a variety of sealing technologies. Traditional sealing technologies include hot water sealing, nickel salt sealing, inorganic salt sealing, etc., but these technologies have problems such as poor sealing effect, complex process, and environmental pollution.

[0003] In recent years, with the development of nanotechnology, nanomaterials have been widely used in the field of metal surface treatment. Graphene is a new type of nanomaterial with high chemical stability and inert surface. When added to the sol, it can form a dense protective layer, effectively preventing external corrosive media from entering the interior of the anodized film. At the same time, the chemical reagents used in its treatment process are relatively few, and most of them are non-toxic or low-toxic substances, which have little impact on the environment, so it has been widely studied and applied. However, in practical applications, graphene sealing technology still faces problems such as poor dispersibility, weak adhesion to the oxide film, complex process, high cost and difficulty in scale, which limits its wide application in industry. Summary of the invention

[0004] The object of the present invention is to overcome at least one disadvantage of the prior art and to provide a sol for anodizing of aluminum alloy and application thereof.

[0005] The present invention proposes an improved graphene sealing technology, which optimizes the dispersion of graphene, enhances its adhesion and simplifies the preparation process through the combination of two-component silane-modified silica sol and titanium sol, thereby overcoming the limitations of the existing technology and providing an environmentally friendly, efficient and economical aluminum alloy corrosion resistance solution.

[0006] The technical solution adopted by the present invention is: In a first aspect, the present invention provides a graphene oxide sol for anodizing of aluminum alloy, which is prepared by the following method: 1) Preparation of silica sol: Anhydrous ethanol, γ-aminopropyltrimethoxysilane, fluorosilane and graphene oxide aqueous solution are mixed, and the pH is adjusted to 4-5 to prepare solvent a; isobutyltriethoxysilane and tetrafluoroethylenetrimethoxysilane are weighed and mixed to obtain a mixed solution, and solvent a is added after heating to 65-70° C., wherein the weight ratio of the mixed solution to solvent a is between 5:5 and 5:6; 2) Preparing titanium sol: Titanate dimethylcarbamate is slowly added to anhydrous ethanol to prepare a titanium precursor liquid, and then deionized water is added thereto, and the pH of the titanium precursor liquid is adjusted to 3-5; 3) The silica sol prepared in step 1) and the titanium sol prepared in step 2) are uniformly mixed in a volume ratio of 1:1 to 1:3.

[0007] In some examples, the volume ratio of anhydrous ethanol to fluorosilane in step 1) is 2:2 to 3:2.

[0008] In some examples, the volume ratio of γ-aminopropyltrimethoxysilane to fluorosilane in step 1) is 4:3 to 1:1.

[0009] In some examples, the volume ratio of dimethylcarbamate titanate to anhydrous ethanol in step 2) is 1:2 to 1:4.

[0010] In some examples, the volume ratio of dimethylcarbamate titanate to deionized water in step 2) is 1:2 to 1:4.

[0011] In a second aspect, the present invention provides an anodizing process for an aluminum alloy, comprising the following steps: 1) The aluminum alloy plate ingot is pre-treated by cleaning, pickling, soaking, and electrochemical polishing; 2) subjecting the pretreated aluminum alloy plate ingot to an electric anodizing treatment for 30 to 40 minutes; 3) Placing the aluminum alloy workpiece after the primary electric anodizing treatment in a chemical etching solution for further etching; 4) The aluminum alloy workpiece after chemical etching is subjected to secondary electric anodizing treatment for 25 to 30 minutes; 5) The aluminum alloy workpiece is immersed in an organic acid solution for 50 to 60 minutes to perform a hole opening treatment, then cleaned, and then immersed in a sol for 5 to 10 minutes, and taken out to solidify. The sol is as described in the first aspect.

[0012] In some examples, the treatment conditions of the electro-anodization in step 2) and step 4) are: placing in a 0.29-0.31 M tartaric acid solution, setting the voltage to 39.5-40.5 V, and the temperature to 0-5°C.

[0013] In some examples, the chemical etching solution is composed of chromic acid and lanthanum nitrate, wherein the concentration of chromic acid in the chemical etching solution is 2.8-3.0 wt.%, and the concentration of lanthanum nitrate is 6-7 wt.%; and / or In the organic acid of step 5), malic acid accounts for 10-12 wt.% and sorbic acid accounts for 15-17 wt.%.

[0014] In some examples, the etching temperature in step 3) is 45-50° C. and / or the etching time is 50-55 min.

[0015] In some examples, the curing treatment in step 5) includes pre-curing at no more than 40° C. for 5 to 10 minutes, and then fully curing at 100 to 110° C.

[0016] The beneficial effects of the present invention are: In some embodiments of the present invention, the two-component silane-modified silica sol can enhance the gel stability and corrosion resistance.

[0017] In some embodiments of the present invention, by using iBTES, the dispersibility of graphene oxide and the corrosion resistance of the material can be improved. iBTES can improve the chemical compatibility of different material surfaces and enhance the adhesion of coatings or composite materials. At the same time, the addition of iBTES makes the coating more uniform and dense, effectively hindering the free diffusion and migration of oxygen and corrosive media in the solution and metal interface, so that the corrosion power is effectively curbed and the corrosion process is slowed down.

[0018] In some embodiments of the present invention, the gel dispersibility and interface binding ability are enhanced by using GPTMS. Since GPTMS introduces amino functional groups, the final coating has strong hydrophilicity and good binding properties. This is conducive to the combination with graphene oxide (GO) in the subsequent surface modification process, providing stronger interface adhesion. At the same time, the combination of low surface energy groups and sol reduces the surface tension, further enhances the dispersibility of GO, enhances the stability of GO in the solution, and avoids the agglomeration of GO.

[0019] In some embodiments of the present invention, the chemical corrosion resistance and adhesion ability of the gel are enhanced by using FVTMS. Its fluorine group gives the material super-hydrophobicity and low surface energy, effectively preventing water droplets and oil stains from adhering, forming a super-hydrophobic coating, enhancing the corrosion resistance of the coating, and improving the tolerance of the material to chemical media such as acids, alkalis, and solvents, and is suitable for harsh environments. At the same time, its higher chemical bond energy enables it to have resistance to ultraviolet radiation and aging resistance, and maintains stable performance when exposed to sunlight for a long time, so that it can be stably combined on the surface of the material. FVTMS can improve the surface smoothness of the coating and reduce the friction coefficient, improve the tactile quality of the material, and adjust the network structure in the sol-gel process to enhance the compactness and durability of the gel.

[0020] In some embodiments of the present invention, the composite system of silica sol and titanium sol significantly improves the interface bonding ability, dispersibility and overall material performance of GO. In terms of interface bonding, TiO 2 Containing active hydroxyl groups, it can not only react with the oxygen groups on the surface of GO, but also provide hydrogen bonds and electrostatic effects through its surface acidity to strengthen the molecular-level bonding. In addition, the Si-O-Si and Ti-O-Ti bonds of silica sol and titanium sol alternately form a three-dimensional inorganic cross-linked network, which embeds GO into the coating structure, thereby significantly improving the mechanical strength and thermal stability of the composite material. In terms of dispersibility, TiO in titanium sol 2 The high specific surface area of ​​the nanoparticles prevents GO from agglomerating through electrostatic repulsion; the composite structure of silica sol and titanium sol also forms an inorganic protective layer around the GO sheets, effectively isolating the particles from direct contact and preventing the sheets from agglomerating. 2 The photocatalytic effect of Si sol slightly reduces GO to reduced graphene oxide (rGO), which enhances the conductivity and electron transport properties. The transparency of Si sol combined with the light absorption characteristics of GO provides good conditions for optical applications such as transparent conductive coatings. Finally, the composite coating exhibits excellent corrosion resistance, mechanical properties and thermal stability in application performance. TiO 2 and SiO 2 The dense cross-linked network formed effectively prevents the penetration of corrosive media, and the conductivity of GO enhances the electrochemical protection mechanism; the flexibility of Si sol combined with the hardness of titanium sol provides a good balance between hardness and toughness, and the uniform dispersion of GO flakes significantly improves the resistance to crack propagation; the thermal stability of inorganic materials also enables the coating to maintain long-term protection at high temperatures.

[0021] In some embodiments of the present invention, after adjusting the pH value and properly controlling the mixing ratio, the silane-modified sol can maintain good stability, avoid gelation or precipitation, and is suitable for coating and film formation. Generally, in the hydrolysis and polycondensation reaction, acidic conditions are more conducive to hydrolysis, and alkaline conditions are more conducive to polycondensation. It is found that when pH < 3, the solution system H + The high content accelerates the hydrolysis process in the reaction, resulting in the generation of a large number of extremely unstable silanols in the system, which will undergo a polycondensation reaction with the hydroxyl groups or other silanols on the silica sol to form oligomers with a lower degree of polymerization, thus obtaining a semi-turbid viscous colloid. When the pH is 4-5, the H+ content in the solution is relatively small, which destroys the balance of the hydrolysis and polycondensation reaction in the sol-gel, causing the reaction to proceed to polycondensation, and it is easy to form a gel. The experimental results show that when the pH is 3-4, the system is stable and a transparent colloid can be generated.

[0022] In some embodiments of the present invention, the modified graphene oxide composite material can improve dispersibility and interfacial bonding. Graphene oxide has a unique two-dimensional structure and a high specific surface area, which can enhance the mechanical properties and thermal stability of the sol. The addition of graphene oxide can significantly improve the crack resistance, friction resistance and conductivity of the coating. In the sol, the presence of graphene oxide can increase the structural robustness of the coating and improve its electrical properties, which is particularly suitable for application scenarios requiring corrosion resistance. DETAILED DESCRIPTION

[0023] The following disclosure provides many different embodiments or examples for implementing different solutions of the present invention.

[0024] The present invention is described in detail below in conjunction with examples, comparative examples and experimental data, but is not intended to identify the key or decisive elements of the present invention or to limit the scope of protection.

[0025] The technical solution of the present invention is further explained below in conjunction with examples.

[0026] Example 1 The preparation method of graphene oxide sol (GO sol) in this embodiment is as follows: 1) Step 1: Preparation of Si sol At room temperature, anhydrous ethanol, γ-aminopropyltrimethoxysilane (GPTMS), fluorosilane (PFOTS) and 0.5 mg / mL graphene oxide aqueous solution were mixed to prepare solvent a, wherein the volume ratio of anhydrous ethanol to PFOTS was between 2:2 and 3:2, and the volume ratio of GPTMS to PFOTS was between 4:3 and 1:1, and the mixture was stirred at a speed of 50 rpm; the pH of the solution was adjusted to 4-5 with nitric acid; isobutyltriethoxysilane (iBTES) and tetrafluoroethylenetrimethoxysilane (FVTMS) are weighed and mixed to obtain a mixed solution, and then the mixture is heated to 65-70° C. and a solvent is added, wherein the weight ratio of the mixed solution to a solvent is between 5:5 and 5:6; 2) Step 2: Preparation of Ti sol At room temperature, dimethyl titanate (TDMAC) is slowly added to anhydrous ethanol, with stirring and dripping, and the volume ratio is between 1:2 and 1:4. Deionized water is prepared and slowly dripped into the titanium precursor liquid. During this process, an appropriate amount of 13%wt hydrochloric acid is added to adjust the pH of the solution to between 3-5, wherein the volume ratio of TTIP to water is usually between 1:2 and 1:4; 3) Step 3: Mix and stir the sols in step 1 and step 2 in a ratio of 1:1 to 1:3 for 2 hours.

[0027] In this embodiment, the graphene oxide sol is used in the following anodizing process to prepare aluminum alloy, and then the prepared aluminum alloy is subjected to corresponding performance tests: 1) Step 1: Preprocessing (a) At room temperature, the aluminum alloy workpiece was placed in acetone, ethanol and deionized water for 40KHz ultrasonic cleaning for 3-4min. (b) The cleaned aluminum alloy workpiece is immersed in 10% by mass phosphoric acid for 10-15 minutes; (c) The aluminum alloy workpiece was electrochemically polished at a constant voltage of 15 V for 5-6 min in a mixed solution of perchloric acid and anhydrous ethanol with a volume ratio of 1:3 to 1:4 at a temperature of 0°C.

[0028] 2) Step 2: Primary anodizing treatment The pretreated aluminum alloy workpiece was placed in a 0.3 mol / L tartaric acid solution, with a voltage of 40 V and an anodizing treatment at a constant temperature of 0-5° C. for 30-40 minutes.

[0029] 3) Step 3: Chemical Etching The aluminum alloy workpiece after the primary electric anodizing treatment is placed in a chemical etching solution for etching at a temperature of 45-50° C. for 50-55 minutes, wherein the concentration of chromic acid in the chemical etching solution is 2.8-3.0 wt.%, and the concentration of lanthanum nitrate is 6-7 wt.%.

[0030] 4) Step 4: Secondary anodizing The aluminum alloy workpiece after chemical etching was placed in a 0.3 M tartaric acid solution again, the voltage was set to 40 V, and anodized for 25-30 min at a constant temperature of 0-5°C.

[0031] 5) Step 5: Hole processing The aluminum alloy workpiece is immersed in a static organic acid solution at room temperature for 10-15 minutes, wherein the concentration of malic acid in the organic acid is 10-12 wt.%, and the concentration of sorbic acid is 15-17 wt.%.

[0032] 6) Step 6: Ultrasonic cleaning The samples were carefully cleaned by ultrasonic cleaning in deionized water for 4-5 min and dried at room temperature.

[0033] 7) Step 7: Sealing The aluminum alloy workpiece after the hole treatment was immediately immersed in the prepared GO sol. The immersion cycle included immersing the sample in the sol for 5-10 minutes, then taking it out at a rate of about 150 mm / min, curing it at room temperature for 5-10 minutes, and repeating this immersion-curing cycle three times. Finally, the sample was cured at 100-110°C for about 2 hours.

[0034] Comparative Example 1 This comparative example is a blank comparison compared with Example 1, that is, boiling water is used as a substitute in the sealing treatment step.

[0035] Comparative Example 2 The difference from Example 1 is that the Si gel in the filling gel is not subjected to the two-component silane modification treatment. The specific preparation method of GO sol is as follows, and the rest is the same as Example 1: 1) Step 1: Preparation of Si sol At room temperature, anhydrous ethanol, γ-aminopropyltrimethoxysilane (GPTMS), fluorosilane (PFOTS) and 0.5 mg / mL graphene oxide aqueous solution were mixed, wherein the volume ratio of anhydrous ethanol to PFOTS was between 2:2 and 3:2; the volume ratio of GPTMS to PFOTS was between 4:3 and 1:1, and stirred at a speed of 50 rpm; 2) Step 2: Preparation of Ti sol At room temperature, dimethyl titanate (TDMAC) is slowly added to anhydrous ethanol, with stirring and dripping, and the volume ratio is between 1-2 and 1-4. Deionized water is prepared and slowly dripped into the titanium precursor liquid. During this process, an appropriate amount of 13%wt hydrochloric acid is added to adjust the pH of the solution to between 3-5, wherein the volume ratio of TDMAC to water is usually between 1:2 and 1:4; 3) Step 3: Mix and stir the sols in step 1 and step 2 in a ratio of 1:1 to 1:3 for 2 hours.

[0036] Table 1 Test results of mechanical properties, corrosion resistance and fluidity of various examples

[0037] By comparing Example 1 and Comparative Example 1, it can be seen that the graphene oxide filling gel treatment reduces the pore size of the anodized film and improves the corrosion resistance.

[0038] By comparing Example 1 and Comparative Example 2, it can be seen that the two-component silane modification treatment improves the dispersibility and interfacial bonding strength of graphene oxide, and improves the stability and corrosion resistance of the gel.

[0039] The above is a further detailed description of the present invention, which should not be regarded as a limitation on the specific implementation of the present invention. For ordinary technicians in the technical field to which the present invention belongs, simple deduction or replacement without departing from the concept of the present invention is within the protection scope of the present invention.

Claims

1. A graphene oxide sol for anodizing of aluminum alloy, characterized in that: Prepared by the following method: 1) Preparation of silica sol: Anhydrous ethanol, γ-aminopropyltrimethoxysilane, fluorosilane and graphene oxide aqueous solution are mixed, and the pH is adjusted to 4-5 to prepare solvent a; isobutyltriethoxysilane and tetrafluoroethylenetrimethoxysilane are weighed and mixed to obtain a mixed solution, and solvent a is added after heating to 65-70° C., wherein the weight ratio of the mixed solution to solvent a is between 5:5 and 5:6; 2) Preparing titanium sol: Titanate dimethylcarbamate is slowly added to anhydrous ethanol to prepare a titanium precursor liquid, and then deionized water is added thereto, and the pH of the titanium precursor liquid is adjusted to 3-5; 3) The silica sol prepared in step 1) and the titanium sol prepared in step 2) are uniformly mixed in a volume ratio of 1:1 to 1:

3.

2. The graphene oxide sol according to claim 1, characterized in that In the step 1), the volume ratio of anhydrous ethanol to fluorosilane is 2:2 to 3:

2.

3. The graphene oxide sol according to claim 1, characterized in that In the step 1), the volume ratio of γ-aminopropyltrimethoxysilane to fluorosilane is 4:3 to 1:

1.

4. The graphene oxide sol according to claim 1, characterized in that In the step 2), the volume ratio of dimethylcarbamate titanate to anhydrous ethanol is 1:2 to 1:

4.

5. The graphene oxide sol according to any one of claims 1 to 4, characterized in that: In the step 2), the volume ratio of dimethylcarbamate titanate to deionized water is 1:2 to 1:

4.

6. An anodizing process for aluminum alloy, characterized in that: The following steps are involved: 1) Pre-treatment of the aluminum alloy plate ingot by cleaning, pickling, soaking, and electrochemical polishing; 2) subjecting the pretreated aluminum alloy plate ingot to an electric anodizing treatment for 30 to 40 minutes; 3) placing the aluminum alloy workpiece after the primary electric anodizing treatment in a chemical etching solution for further etching; 4) subjecting the aluminum alloy workpiece after chemical etching to a secondary electric anodizing treatment for 25 to 30 minutes; 5) The aluminum alloy workpiece is immersed in an organic acid solution for 50 to 60 minutes for opening treatment, then washed, and then immersed in a sol for 5 to 10 minutes, taken out and solidified, wherein the sol is as described in any one of claims 1 to 5.

7. The use according to claim 6, characterized in that: The treatment conditions of the electric anodization in step 2) and step 4) are: placing in a 0.29-0.31 M tartaric acid solution, setting the voltage to 39.5-40.5 V, and the temperature to 0-5° C.

8. The use according to claim 6, characterized in that: The chemical etching solution is composed of chromic acid and lanthanum nitrate, wherein the concentration of chromic acid in the chemical etching solution is 2.8-3.0 wt.%, and the concentration of lanthanum nitrate is 6-7 wt.%; and / or In the organic acid of step 5), malic acid accounts for 10-12 wt.% and sorbic acid accounts for 15-17 wt.%.

9. The use according to claim 6 or 8, characterized in that: In step 3), the etching temperature is 45-50° C. and / or the etching time is 50-55 min.

10. The use according to claim 6, characterized in that: The curing treatment in step 5) includes pre-curing at a temperature not exceeding 40° C. for 5 to 10 minutes and then fully curing at 100 to 110° C.

Citation Information

Patent Citations

  • Oxidized graphene / sol-gel sealing technology for anodic oxidized film

    CN109338433A

  • Method for preparing micro-arc oxidation / graphene oxide / silane composite film on the surface of aluminum alloy

    CN110396709A

  • Hydroxyl graphene-modified plating sealants and preparation methods thereof

    US20190241751A1